Underpinning excellence in higher education: Exploring self-regulatory skills of high performing academic students - K., Faridah Mydin (Advances in Social Sciences Research Journal, 2017)
Learner autonomy and independence are the key to a student’s success at university. Students need to be self-directed, proactive and in charge of their own learning process. Framed within the social cognitive perspective, this study sought to explore the nature and the use of self-regulatory skills employed by students in learning and extracurricular activities. This research utilised a qualitative research design. Semi-structured interviews were carried out on fifteen 4th year undergraduate students studying in one of the established research universities in Malaysia to elicit information on their self-described self-regulation skills and to examine its potential link to academic success and strong achievement in extracurricular activities. Data were analysed using thematic analysis to identify themes that emerged from the interviews. Three main self-regulation strategies were identified: goal attributed strategies, self-reflection, and self-management. The results show that high achieving students employ a range of self-regulation strategies.